-6x-36=-2(-3+6x)

Simple and best practice solution for -6x-36=-2(-3+6x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x-36=-2(-3+6x) equation:


Simplifying
-6x + -36 = -2(-3 + 6x)

Reorder the terms:
-36 + -6x = -2(-3 + 6x)
-36 + -6x = (-3 * -2 + 6x * -2)
-36 + -6x = (6 + -12x)

Solving
-36 + -6x = 6 + -12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12x' to each side of the equation.
-36 + -6x + 12x = 6 + -12x + 12x

Combine like terms: -6x + 12x = 6x
-36 + 6x = 6 + -12x + 12x

Combine like terms: -12x + 12x = 0
-36 + 6x = 6 + 0
-36 + 6x = 6

Add '36' to each side of the equation.
-36 + 36 + 6x = 6 + 36

Combine like terms: -36 + 36 = 0
0 + 6x = 6 + 36
6x = 6 + 36

Combine like terms: 6 + 36 = 42
6x = 42

Divide each side by '6'.
x = 7

Simplifying
x = 7

See similar equations:

| 48r^5b^8+18r^4=0 | | 180=(2x^2-2)x | | 112x^4-280x^3+175x^2=0 | | -6x-18=-108 | | 180=2x^2-2x | | ln(x)-x=35 | | 5x^2=3x^2+50 | | 2x-25=12x+60 | | 1/4M8 | | 8(7a+2)-6a=-2a-36 | | 2=(4y+1) | | 4/5x=6/5 | | g=4t+6 | | 4=16+6x | | 0=80x^3-45x | | 92/100 | | 9q^2-64=0 | | g(x)=80x^3-45x | | 4y+14=6y-2 | | 3x+x^3=108 | | 24a^3-168a^2+294a=0 | | 2cos^2x-9cosx=5 | | 14+2x=56 | | 10x=9x+4 | | 0=-16t^2+20t+0.5 | | 4(4x+19)-3x=0 | | 3x^2-144x+35=0 | | (H^4)= | | x^4-8x^3-16x^2+16x-16=0 | | -16x+72-3x=0 | | 90+(5x-2)=180 | | 17p= |

Equations solver categories